Optimization of Ultrasound-Assisted Extraction of Glucosinolates from Upcycled Cauliflower Using Response Surface Methodology - Hana Derbew Gedif; Tess Astatkie; Joanna Tkaczewska; H. P. Vasantha Rupasinghe (Molecules)
This study aimed to optimize the ultrasound-assisted extraction (UAE) process using food-grade ethanol to recover glucosinolates from upcycled cauliflower through response surface methodology. The optimized extraction process was compared with traditional extraction using maceration with solvents such as methanol and acetone. The optimum UAE conditions identified for extracting glucosinolates from upcycled cauliflower were: 42% ethanol as solvent at 43 °C for 30 min. The total glucosinolate content recovered was 7400 μg sinigrin equivalence (SE)/g dry weight (DW) of biomass. The ultra-pressure liquid chromatography–electrospray ionization-mass spectrometry (UPLC-ESI-MS) analysis confirmed that the optimized UAE yielded the highest levels of glucoraphanin (1.31 ± 0.12 μg/g DW of biomass) and sulforaphane (28.2 ± 3.34 μg/g DW of biomass). The extracts possess greater antioxidant activity as determined by ferric reducing antioxidant power and DPPH radical scavenging activity. The optimized UAE process significantly enhanced the extraction of valuable phytochemical molecules from the upcycled cauliflower. Further studies should focus on evaluating their therapeutic and preventive potential for applications in nutrition and health.